An An Intertextual Analysis of “Menombak Matahari”, “Sarpakuda”, and Babad Mangir Suradipura - Sulthan, Faqih; Wijayatiningsih, Testiana Deni (Faculty of Language and Literature, University of Surakarta, 2024)
The creation of a new text is highly influenced by previous texts, known as intertextual relationships. For instance, the short stories